L’art transgenre, vers d’autres expériences corporelles du temps - Luc Schicharin (Glad!)
This article compares the representation of time in its relation to the transformation of the body, in the hegemonic (artistic) culture and in the semiological content of transgender works. First, the study focuses on the criticism of the before-after trope of transsexuality in Yishay Garbasz’s work "Becoming". According to our hypothesis, this visual dialectic derives from an evolutionary temporal norm appeared in the nineteenth century (with Darwin and the invention of cinema). Next, Wynne Neilly’s "Female-to-‘Male’" installation exposes the artist’s transgender "second puberty" experience, turning away from a hetero-cisnormative chronobiology focused on sexual maturity and reproduction. Finally, the performances of Kris Grey’s "Untitled" and Cassils’ "Cuts: A Traditional Sculpture" question the body as a living sculpture: they deconstruct the idea that the medical identification of sex is "the fruitful moment" (Lessing) of gender and the eternal "biological bedrock" (Freud) of subjectivity. Transgender art thus invites us to think of other bodily temporalities.